Scarless wound healing: Transitioning from fetal research to regenerative healing - Moore, Alessandra L. (Wiley Interdiscip Rev Dev Biol, 2018)
Since the discovery of scarless fetal skin wound healing, research in the field has expanded significantly with the hopes of advancing the finding to adult human patients. There are several differences between fetal and adult skin that have been exploited to facilitate scarless healing in adults including growth factors, cytokines, and extracellular matrix substitutes. However, no one therapy, pathway, or cell subtype is sufficient to support scarless wound healing in adult skin. More recently, products that contain or mimic fetal and adult uninjured dermis were introduced to the wound healing market with promising clinical outcomes. Through our review of the major experimental targets of fetal wound healing, we hope to encourage research in areas that may have a significant clinical impact. Additionally, we will investigate therapies currently in clinical use and evaluate whether they represent a legitimate advance in regenerative medicine or a vulnerary agent.